Radiation dose at coronary CT angiography: second-generation dual-source CT versus single-source 64-MDCT and first-generation dual-source CT - Fink, Christian; Kriššák, Radko; Henzler, Thomas; Lechel, Ursula; Brix, Gunnar; Takx, Richard A. P.; Nance, John W.; Abro, Joseph A.; Schönberg, Stefan; Schoepf, U. Joseph (American journal of roentgenology, 2011)
OBJECTIVE. The purpose of this study was to assess the radiation doses of different coronary CTA (CTA) protocols: second-generation dual-source 128-MDCT, first-generation dual-source 64-MDCT, and single-source 64-MDCT. MATERIALS AND METHODS. Thermoluminescent dosimetry was used to determine scanner-specific dose coefficients for standard coronary CTA of an anthropomorphic phantom. These coefficients were used to estimate the effective doses (EDs) of retrospectively gated, prospectively triggered, and prospectively triggered high pitch coronary CTA performed at 100 and 120 kV. The coronary CTA protocols used in imaging of 43 patients undergoing dual-source 128-MDCT were analyzed for ED, image quality, and signal-to-noise ratio. RESULTS. Regardless of coronary CTA protocol and CT system, imaging at 100 kV lowered the ED 40-50%. In retrospectively gated 120-kV coronary CTA, the ED ranged from 5.7 to 10.7 mSv and was approximately 50% lower with single-source 64-MDCT than with either DSCT protocol. In prospectively triggered 120-kV coronary CTA, the ED ranged from 3.8 to 4.0 mSv. The lowest ED of all protocols (1.3 mSv) was observed in prospectively triggered high-pitch 100-kV coronary CTA performed with dual-source 128-MDCT. Patient measurements showed similar dose reductions for prospective triggering and low voltage settings without an influence on signal-to-noise ratio or image quality. CONCLUSION. A combination of prospective triggering with low voltage settings is an effective measure for reducing the ED of coronary CTA to values of 2-4 mSv independent of scanner system. Further dose reduction to nearly 1 mSv can be achieved with high-pitch prospectively triggered coronary CTA.
Gesehen am 11.05.2023
nach Überarbeitung angenommen September 24, 2010